Context affects L1 but not L2 during bilingual word recognition: An MEG study - Pellikka, Janne; Helenius, Päivi; Mäkelä, Jyrki P.; Lehtonen, Minna (Brain and language, 2015)
•Bilingual spoken word recognition was studied with magnetoencephalography.•We manipulated word presentation context in late Finnish–English bilinguals.•The results showed an asymmetric language switching cost in the N400m response.•Context affected word recognition only in the L1, suggesting inhibitory processes.•Models allowing context to affect word recognition processes are supported. How do bilinguals manage the activation levels of the two languages and prevent interference from the irrelevant language? Using magnetoencephalography, we studied the effect of context on the activation levels of languages by manipulating the composition of word lists (the probability of the languages) presented auditorily to late Finnish–English bilinguals. We first determined the upper limit time-window for semantic access, and then focused on the preceding responses during which the actual word recognition processes were assumedly ongoing. Between 300 and 500ms in the temporal cortices (in the N400m response) we found an asymmetric language switching effect: the responses to L1 Finnish words were affected by the presentation context unlike the responses to L2 English words. This finding suggests that the stronger language is suppressed in an L2 context, supporting models that allow auditory word recognition to be affected by contextual factors and the language system to be subject to inhibitory influence.